Ernst Bloch's speculative materialism : ontology, epistemology, politics - Moir, Cat, 1983- (Historical materialism book series, 2020)
"In Ernst Bloch's Speculative Materialism: Ontology, Epistemology, Politics, Cat Moir offers a new interpretation of the philosophy of Ernst Bloch. The reception of Bloch's work has seen him variously painted as a naïve realist, a romantic nature philosopher, a totalitarian thinker, and an irrationalist whose obscure literary style stands in for a lack of systematic rigour. Moir challenges these conceptions of Bloch by reconstructing the ontological, epistemological, and political dimensions of his speculative materialism. Through a close, historically contextualised reading of Bloch's major work of ontology, Das Materialismusproblem, seine Geschichte und Substanz (The Materialism Problem, its History and Substance), Moir presents Bloch as one of the twentieth century's most significant critical thinkers"--